Reward effects and incentive effects on the labor market: Empirical evidence for European countries - Friedrich L. Sell; Michael Öllinger (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2017)
In this investigation, a political economy model of the labor market is proposed, where unions offer their (old and new) affiliates the combinations between the average real wage level and the standard deviation of wages or salaries. Globalization and other forces, however, have made it recently more difficult to the unions to pursue their policy in the backdrop of a declining union density. This has been established empirically for selected European countries. In an econometric exercise, we have also tested directly the impact of changes in real wages, minimum wage rate, and the effect of 90 to 10 decile ratio on the change in the degree of affiliation, which the unions were able to achieve in the recent past.
Keywords: J51; D72; J31; O15; 330; political Economy of the labor market; union density; wage dispersion; average and minimum wages